PENERAPAN STRATEGI PEMBELAJARAN KOOPERATIF INVESTIGASI KELOMPOK DALAM MENINGKATKAN KETERAMPILAN SOSIAL PESERTA DIDIK DENGAN HAMBATAN EMOSI DI SMA BPI 1 BANDUNG - affan afrian pratama, - (2022)
This study aims to determine the application of the Group Investigation Cooperative Learning Strategy in Improving the Social Skills of Students with Emotional Barriers at SMA BPI 1 Bandung. The learning strategy given by the teacher in the field is too teacher center where students are not conditioned to think and exchange ideas with each other. This causes students to be divided into active and inactive. This group investigative strategy involves a lot of two-way interaction, and grouping students with various characters in order to better know the strengths and weaknesses of each other. Research subjects are students at SMA BPI 1 Bandung. The data obtained were analyzed through descriptive statistics and displayed in the form of graphs and tables. The results of the study showed that there was a positive influence in increasing the ability of social skills. In this study, it is recommended that schools provide services to protect children with learning difficulties due to their differences.